PENDIDIKAN RAMAH ANAK PERSPEKTIF HADITS NABI - Ali Mohtarom (Mu'allim, 2021)
The pattern of child - friendly education is actually creating a safe, comfortable, healthy, conducive environment, accepting all the shortcomings of children and respecting the potential of children. The principles of child - friendly schools are: non - vio lent, non - discriminatory, the best education for children, the right to grow and develop and respect for children's opinions. Islam has a perspective on friendliness towards children, which emphasizes the recommendation to be merciful to children. As menti oned in the hadith of the Prophet: "Whoever does not love the little one among us and does not understand the rights of the greater one among us, then he is not from our group." (HR. Abu Dawud). This study uses descriptive qualitative research methods. Research aimed at describing and analyzing phenomena, events, social activities, attitudes, beliefs, perceptions, and thoughts of people individually and in groups "The Prophet sallallaahu 'alaihi wa sallam kissed Al - Hasan bin Ali, and on the side of the P rophet there was Al - Aqro bin Haabis At - Tamimiy who was sitting, So Al - Aqro ' said, "I have 10 children, none of them I have ever kissed." he will not be blessed." (Narrated by Al - Bukhari and Muslim). Even when the children made a mistake the Messenger of A llah guided them in a gentle manner. It was narrated from Abu Rafi bin Amr Al Ghifari that he said, "I threw stones at the Ansar palm trees. Then they brought me to the Messenger of Allah, sallallaahu 'alayhi wa sallam, he asked, "Son, why are you pelting their date palms? answered because he was hungry, O Messenger of Allah. He said, "Do not throw palm trees, but eat what falls from the trees. Then he rubbed his hand over my head and said, "May Allah fill you and satisfy you" (HR. Tirmidhi)